Classic Fairy Tales : The Three Billy Goats Gruff - Alligator Books Limited (Alligator Books Limited, 2004)
Once upon a time there were three billy goats. First there was the little billy goat Gruff, who was the smallest of the three.
Keywords: Tales / Fairy / Three Billy Goats Gruff